원심 다익홴의 유동에 대한 컷 오프 각도의 영향 - 강경준; 신유환; 이윤표; 김광호 (한국유체기계학회, 2010)
This study investigated on details of flow characteristics of a multi-blade fan for domestic ventilation. Experiments and analysis were carried out to describe on flow pattern with variations of cut-off angle near the scroll housing throat, which were performed by PIV measurement for the flow field and by total pressure probes. The stagnation point at cut-off region of the fan moves to the exit of the scroll housing as the cut-off angle increases. The movement of stagnation point and the variation of throat area of the scroll housing influence to the distribution of velocity magnitude at the exit of the fan. Furthermore, a large distortion of the velocity distribution at the scroll exit causes to increase mixing loss along the flow path.